EFEKTIVITAS KOMUNIKASI WEBSITE SISTEM INFORMASI PERHITUNGAN SUARA (SITUNG) KOMISI PEMILIHAN UMUM (KPU) DALAM DALAM MEMBERIKAN INFORMASI HASIL PEMILIHAN UMUM 2019 BAGI MASYARAKAT KOTA PEKANBARU - Yanti, Tamara Putri; ", Suyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
General Election Comission (KPU) calculation is an electronic vote acquisition (e-recap) recapitulation activity as a temporary data for comparison of official results by the KPU which continues to use manual and tiered recapitulation in accordance with the mandate of the Act. However, with the existence of Situng the public can find out the provisional results and also as a means of control for election organizers and the public, so there is no recapitulation fraud at the District Election Committee (PPK), district / city, and provincial levels.The purpose of this research was to know the communication evaluation result of the Situng KPU website providing information on the result of the 2019 elections. The people of Pekanbaru were chosen because of the highest population density in Riau Province. In terms of supporting facilities and infrastructure, the people of Pekanbaru City can easily get information quickly through the media, especially online media               This research uses quantitative research methods with data collection techniques through the distribution of questionnaires through the internet and directly to 96 respondents based on probability sample techniques. Data analysis techniques in this study use descriptive statistical techniques.And also using calculations through SPSS software version 21.0        The results of this research state that the Situng KPU website is effective as a result of the 2019 Election with the accumulated value of the effectiveness of the SUTUNG KPU. Measuring the scale of the communication effectiveness of the "Election Commission's Information Counting Information System" website uses the variable effectiveness of Hardjana Andre's communication consisting of six indicator. The value obtained by the user indicator (receiver or user) is 2.93 and enter the effective scale, the value of the message content indicator is 2.76 and enter the effective scale, the value obtained by the communication media (media) is 3.13 which means effective, the value for the format of the message (format) is 3 that fall into the effective category, the value of the message source (source) is 2.58 and belongs to the effective category and the last value for the timekeeping indicator is 3.16 which means effective.Keyword : Effectiveness communication, Website Situng, and General Election Comission(KPU)